Continuing education activities improve dentists' self‐efficacy to manage oral mucosal lesions and oral cancer. (30th August 2020) - Braun, Liliana W.; Martins, Marco A. T.; Romanini, Juliana; Rados, Pantelis V; Martins, Manoela D.; Carrard, Vinicius C.
Abstract: Objectives: This cross‐sectional study aims to evaluate whether Continuing Education Activities (CEA) influence dentists' behaviour in relation to oral lesions. The secondary aim is to assess the association between dentists' perception of learning adequacy and self‐efficacy for oral mucosal lesion management. Methods: A self‐administered online questionnaire was conducted on dentists working at the public health system of Rio Grande do Sul State, Brazil. The questionnaire included questions pertaining to perception of adequacy for oral diagnosis classes upon graduation, participation in oral cancer CEA and self‐efficacy in managing oral mucosal lesions. Results: 221 dentists from 91 municipalities answered the questionnaire. Most participants were female (71.5%) with a mean age of 38.3 years. Perception of learning as adequate during undergraduate coursework was associated with self‐efficacy to diagnose, biopsy, and treat oral mucosal lesions ( P  < .05, Chi‐squared test). However, 83.3% of dentists considered the time devoted to these topics prior to graduation insufficient. The frequency of oral lesion detection was related to self‐efficacy to treat oral lesions and detecting oral cancer ( P  < .05, Chi‐squared test). Among dentists who detected oral lesions frequently, 88.9% had attended CEA, whereas 11.1% of them had never attended these activities. Conclusions: CEA may improve awareness and efficacy of primary healthcare professional's detection of oral cancer.